Depression and anxiety during the year before death from cancer - Magill, N; Walker, J; Symeonides, S; Gourley, C; Hobbs, H; Rosenstein, D; Frost, C; Sharpe, M (Elsevier, 2022)
Objective: Previous studies of depression and anxiety during the year before death have reported different findings. We therefore aimed to study depression and anxiety in patients who had died from cancer and had previously attended cancer clinics.